The impact of electricity investment on inter-regional economic development in Indonesia: An Inter-Regional Input-Output (IRIO) approach - Albertus Girik Allo; Inayati Nuraini Dwiputri; Marcus Maspaitella (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
Electricity is a development priority for low and middle income countries, including Indonesia, especially in the households living in suburban and rural areas. By 2020, Indonesia's electrification ratio has reached 96.71%. However, there were 433 villages that did not have electricity, most of which were located in eastern Indonesia (Papua, West Papua, East Nusa Tenggara, and Maluku). Investment in the electricity sector will drive regional economic growth. This research attempts to figure out the impact of investment in electricity on economy. This study used Indonesian inter-regional Input-Output data. The method used in this study was the Interregional Input-Output (IRIO) model. The analysis shows that electricity impacted not only the territory being built but also other regions in Indonesia. Electricity industry investment in Indonesia have been able to provide a multiplier effect on the economy as many as 3.11. Java region gets the greatest benefit from electricity development in Indonesia. This was rationally acceptable due to the fact that most of the industry was located in this region. This causes a development gap between Java and outside Java. It is necessary to accelerate reallocate several national strategic industries on various islands in Indonesia based on the advantages of each region and to strive for areas that are still "dark" to have electricity.JEL Classification E22; L94; R15